Implementation Agreement By Mixed Marriage Based On Act No. 1 of 1974 Concerning Marriage After Constitutional Court Ruling No. 69 / PUU-XIII / 2015 (Study of Notary Role) - Riyanto Riyanto; Wachid Aryanto; Arief Cholil (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2018)
Abstract. The bride and groom's candidate before the marriage takes place, can make a